Colorectal cancer - Nicum, S; Midgley, R; Kerr, D (2003)
Colorectal cancer (CRC) is one of the leading causes of mortality and accounts for approximately 200 000 deaths per year in Europe and the USA. Chemotherapy and radiotherapy have established roles in the treatment of colorectal cancer and can contribute to cure rate, prolongation of survival, reduction of local rates of recurrence and enhanced quality of life in patients with advanced disease. However, over the past few years there have been major advances in our understanding of the molecular basis of this tumour and its progression from adenoma to carcinoma that hold potential for translation into novel strategies for the treatment of CRC. Furthermore, newer agents directed against different intracellular targets have also been shown to be efficacious in CRC treatment. Such improvements should continue to lead to increased cure rates in early disease and better overall survival in advanced cases. The aim of this review is to provide an overview of the pathogenesis of CRC and to present the evidence base for chemotherapy and some of the novel strategies that are currently being evaluated in phase I and II trials.